Research progress in the surgical treatment of anorectal stricture in Crohn disease - Jin-Rong LI; Li-Bei ZHU; Ze-Peng CHEN; Li-Chao QIAO; Yu-Xia GONG; Bai-Lin YANG; Ping ZHU (Yixue xinzhi zazhi)
Anorectal stricture is the most challenging complication of perianal Crohn disease, and it often has a severe negative impact on the patient's quality of life. Limited by the narrow anatomical space around the anorectum, how to address the stricture symptoms while preserving sphincter function and avoiding complex surgery is one of the clinical challenges for surgeons. There are few studies on anorectal stricture in Crohn disease, and how to provide patients with the best clinical evaluation and treatment options is an urgent issue. The article summarizes the endoscopic and surgical treatments for anorectal stricture in Crohn disease in the hope that it will provide a useful reference for clinical decision-making by specialists.